2019
DOI: 10.3748/wjg.v25.i18.2149
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the esophageal microbiota in Barrett's esophagus and esophageal adenocarcinoma

Abstract: The incidence of esophageal adenocarcinoma (EAC) has increased in recent decades, and its 5-year survival rate is less than 20%. As a well-established precursor, patients with Barrett's esophagus (BE) have a persistent risk of progression to EAC. Many researchers have already identified some factors that may contribute to the development of BE and EAC, and the identified risks include gastroesophageal reflux (GER), male sex, older age, central obesity, tobacco smoking, Helicobacter pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 91 publications
(169 reference statements)
3
78
2
6
Order By: Relevance
“…Results obtained from other studies revealed that Veillonella, Prevotella, Neisseria, and Fusobacterium are abundantly present in patients with BE. These bacteria were not detected in the esophagus of healthy subjects, and recently published studies by other authors confirmed these results [404,407].…”
Section: Cancers Of Digestive Systemsupporting
confidence: 66%
“…Results obtained from other studies revealed that Veillonella, Prevotella, Neisseria, and Fusobacterium are abundantly present in patients with BE. These bacteria were not detected in the esophagus of healthy subjects, and recently published studies by other authors confirmed these results [404,407].…”
Section: Cancers Of Digestive Systemsupporting
confidence: 66%
“…However, few information exist on upper GI, while the majority of studies have focused on sites easier and less invasive to sample. Moreover, the available studies have not been designed to comprehensively evaluate through 16S-based amplicon sequencing the whole normal-BE-EAC human mucosal spectrum and thus have yielded mixed results [24,39,40]. In the present study, we report not only…”
Section: Discussionmentioning
confidence: 81%
“…Puerarin, the main component of GQD, can increase the abundance of Akkermansia to promote the expression of ZO-1 and occludin, thereby protecting the intestinal barrier function[ 52 ]. Activation of the LPS–TLR4–NF-κB pathway has been shown to be involved in inflammatory processes and malignant transformation[ 53 ]. SCFAs are present in metabolites of Bacteroides and Prevotella .…”
Section: Discussionmentioning
confidence: 99%